Standardization of the new immunohistochemical protocol to identify Helicobacter pylori from gastric biopsies and contrast against Hematoxylin-Eosin - Mejía-Parra, Jorge Luis Jhoao (2020)
Objetive. Standardize a new immunohistochemical protocol to identify Helicobacter pylori in gastric biopsies. Materials and Methods: the work was carried out in three phases. The first phase makes use of polyclonal rabbit Anti-H. pylori antibodies as a primary antibody for the labeling of said bacteria, in addition to an EnVision FLEX / HRP polymer for labeling in gastric biopsies. In the second, the immunostaining contrast was modified with the Harris Hematoxylin and Eosin Y dyes, in order to more clearly appreciate the cytomorphology of the gastric tissue to be examined and the possible pre-malignant histological changes. Finally, the results were evaluated against Hematoxylin and Eosin (H&E) staining. Results and Discussion: We show that by carrying out the new immunohistochemistry protocol, it facilitates the identification of H. pylori and, in turn, allows the evaluation of cytomorphological changes in gastric biopsies. The establishment of this protocol will allow an adequate study of the association of H. pylori infection and pre-malignant histological changes in gastric tissue.